Contracts Adjustment under Bilateral Information Updating in a Supply Chain - Xinhui Wang; Yingsheng Su; Zihan Zhou; Yiling Fang (Complexity)
This paper investigates contracts adjustment between one manufacturer and one retailer under bilateral information updating. The manufacturer incurs uncertain production cost and the retailer faces uncertain demand, but they can acquire independent signals to update production cost and demand, respectively. They commit an initial agreement on an initial wholesale price, minimum order quantity, and information sharing as well as the transfer payment and decisions adjustment when information is updated. We find that due to the joint impact of production cost variation and market variation, the manufacturer may not decrease (increase) her wholesale price when the updated production cost is lower (higher) than expected. The retailer places an additional order even if the wholesale price rises when the market outlook is good, but places an order with the minimum order quantity even if the wholesale price falls when the market outlook is bad. Secondly, for a certain level of information accuracy of the production cost and market demand, the retailer is always better off with information updating, but the manufacturer may be worse off with information updating when facing a bad market outlook. Thirdly, when information accuracy of the production cost and market demand varies, the manufacturer only benefits from a high accuracy of production cost. Profits of the retailer and the supply chain are increasing (decreasing) with accuracy of production cost if the updated production cost is larger (smaller) than expected.